INTEGRATING LOCAL CULTURE INTO WEB-BASED ELT FOR YOUNG LEARNERS: A SYSTEMATIC LITERATURE REVIEW OF RECENT TRENDS AND PRACTICES - Heriyanto, Eko; Fitriati, Sri Wuli; Sakhiyya, Zulfa (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This study aims to explore and analyze best practices for integrating local culture into web-based English language teaching for young learners through a systematic review of 10 articles published between 2013 and 2023. Using the PRISMA framework, the study found that incorporating local culture into the English language curriculum significantly boosts students’ motivation, engagement, and communication skills. Materials emphasizing local culture also encourage students to understand and appreciate their cultural identity while improving their language skills in a global context. Although challenges such as native-speakerism attitudes exist, information and communication technologies can support this integration by providing access to more diverse and relevant materials. The study recommends developing culturally responsive teaching materials and applying inclusive methodologies in teaching practices. These findings are expected to help educators and policymakers create more effective and relevant learning environments for students in an increasingly interconnected global era.